MENUMBUHKAN PRODUKTIVITAS DAN KINERJA USAHA KAIN TIE DYE UMKM SRIKANDI DI DESA DONOHUDAN : - - Legowo Dwi Resihono; Retnoningrum Retnoningrum; Luluk Takari; Jimo Jimo (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
Increasing public awareness of increasing local wisdom products is in line with activities to preserve nature, this has made the trend of an environmentally friendly lifestyle very popular and increasingly spreading to various business sectors. One of the products of local wisdom, namely batik, in the development of a relatively new manufacturing technique, ecoprint batik is contemporary batik. One of the batik ecoprint SMEs in Boyolali is Srikandi SMEs precisely in Dohohudan Ngemplak Boyolali. This SMEs can be categorized as a start-up business managed by housewives in Donohudan Village. The local village government strongly supports SMEs activities in the hope of improving the standard of living of the community during the Covid 19 Pandemic like this. Community roles and contributions are needed in economic empowerment. The result of the activity is the implementation of community activities in developing skills in managing Srikandi's SMEs management activities in growing their performance productivity through SMEs management training (entrepreneurship, simple financial management, marketing strategy and e-commerce). This activity is expected to increase the competitiveness of SMEs Srikandi (batik ecoprint) with similar SMEs. The activity was carried out for one week, the training participants gave positive and enthusiastic responses to developing these batik products Keywords: MSME, Ecoprint, management